Does apple canker develop independently on leaf scars of a single apple shoot? - Xu, Xiangming; Olivieri, Leone; Gange, Alan C.; Vorster, Lizelle; Rice, Don; Campbell, Rebecca E.; Walter, Monika (New Zealand Plant Protection, 2021)
European apple canker, caused by Neonectria ditissima, causes serious damage to apple trees, particularly young trees. Canker management is difficult because of the limited availability of effective fungicides, the long latency period, inoculum abundance and host resistance in commercial cultivars as well as the need for costly manual pruning interventions. To understand disease aggregation for more effective pruning management, we assessed whether canker infection and subsequent lesion development on leaf scars are independent from each other on the same shoot. Four inoculation experiments were conducted: one in glasshouse, and three in orchards. On each shoot, 10 consecutive leaf scars were inoculated and assessed for visible cankers over time in situ. Number of cankers developed per shoot as well as spatial distribution of these cankers within a shoot was statistically analysed. Most data of the number of visible canker lesions on a single shoot failed to fit binomial distributions (indicator for independence) and were fitted much better by beta binomial distributions. In a number of cases (4–20%), there appeared to be positive association between lesion development on neighbouring leaf scars. However, in one experiment where laboratory incubation and isolation of N. ditissima from inoculated but asymptomatic leaf scars (after eight months’ field incubation) were used the results suggested independence of canker development on a single shoot. We conclude that apparent aggregation of canker lesions on individual shoots is likely to originate from host responses. Such aggregation of canker lesions on individual shoots should be taken into consideration for field disease assessment and management.